Relationship between Anxiety and Depression with Quality of Life after Coronary Artery Bypass Graft - M Parsamehr; A Afshani; F Nikoo (Iran University of Medical Sciences, 2015)
Abstract Background & Aim: Anxiety and depression could lead to physical or psychological consequences and reduce the quality of life of patients. The present study was carried out to determine the relationship between anxiety and depression with quality of life in patients undergoing coronary artery bypass graft. Material & Methods: It was a cross-sectional study. The sample consisted of 102 patients who had been undergone coronary artery bypass graft (CABG) in Azahra hospital of Shiraz city. The patients were recruited by convenience sampling method. Data was collected by standardized hospital anxiety and depression scale (HADS) and global Quality of Life questionnaire (WHOQOL-BREF) and analyzed by statistical tests of Pearson correlation, t-test and hierarchical multiple regression using SPSS-PC (v. 20). Results: There was a significantly negative relationship among depression and anxiety with quality of life (P<0.001). Quality of life was also significantly associated with sex (p<0/001), educational level (p<0/033), income (p<0/001) and occupational status (p< 0/001). Hierarchical multiple regression analysis showed that the sociodemographic variables (step1) have explained %14/3 and clinical variables (step2) explained %70/4 of the variance of the quality of life. Conclusion: Regarding the frequency of anxiety and depression among these patients and its negative impact on treatment outcome and quality of life of patients with coronary artery diseases, performing appropriate screening and therapeutic approaches for this group of patients is suggested.